Digital Communication Transformation in Micro Tourism Enterprises: Adaptation Strategies and Media Literacy Barriers - Subekti, Priyo; Novianti, Evi (Ikatan Sarjana Komunikasi Indonesia, 2025)
This paper investigates the adaptive tactics, expectations, and obstacles micro-entrepreneurs (UMKM) in coastal tourism zones of Indonesia encounter in adopting digital communication tools. This study intends to grasp how local and migrant business people experience digital transformation. The study takes a qualitative descriptive technique to find patterns of communication behaviour and readiness toward digitalization rather than suggesting a particular hypothesis. In-depth interviews and field observations with chosen informants representing different tourism-related micro-enterprises—including apparel stores, food vendors, and guesthouse operators—provided data. Participants were classified as local or migrant business owners. Emphasizing data reduction, data display, and conclusion drawing, Miles and Huberman's methodology was used to thematically evaluate the data. The results show notable variations in digital adaptation between local and migrant business owners. While native players depend mostly on conventional word-of-mouth and direct consumer contacts, migrant entrepreneurs are more proactive and savvy in exploiting internet channels like Agoda or Instagram. Key expectations the report also underlines are the requirement of focused training, ongoing mentoring, and equitable access to digital infrastructure and government support. Among the obstacles found are low digital literacy, psychological resistance, information access restrictions, and policy execution structural inequities. Digital communication revolution among UMKM, this study finds, is not just about technological acceptance but also about cultural adaptation, psychological preparation, and institutional support—emphasizing the need of inclusive, community-based communication approaches.